L’image de la France dans Freie Gedanken zur Verbesserung der menschlichen Gesellschaft (1752) de Johann Michael von Loen - Catherine Julliard (Recherches Germaniques)
The study focuses on the image of France that emerges from the various essays by J.M. von Loen (1694-1776), which were published in the Freie Gedanken zur Verbesserung der menschlichen Gesellschaft (1752) and hitherto little discussed by critics. It tries to assess the part of gallophobia which characterizes those essays, in the spirit of the anti-French libels of the 17th century. The first part of the study focuses on the psychological portrait of the French, which oscillates between nuances and stereotypes. The second part is devoted to the denunciation of French hegemony which takes different forms. The final part shows how Loen pleads for change in the balance of European Powers, this balance being threatened by France.